2021
DOI: 10.12998/wjcc.v9.i13.3120
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac, pulmonary cement embolism in a 67-year-old female after cement-augmented pedicle screw instrumentation: A case report and review of literature

Abstract: BACKGROUND We report a case of Intracardiac, pulmonary, and intravenous cement embolism after cement-augmented pedicle screw instrumentation in treating spondylolisthesis underlying osteoporotic bone, which was successfully managed by conservative treatment. We describe the treatment and outcome of the patient, hoping to shed light on the management of bone cement embolism. CASE SUMMARY A 67-year-old female suffered from progressive low back pain and numbness in lower e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The patient was treated with anticoagulation therapy and had no further symptoms, including syncope; thus, there was no need for additional interventions. Liang et al 19 suggested that cardiopulmonary embolism should be managed by conservative treatment under close monitoring. In patients who develop mild clinical manifestations with a stable hemodynamic status, conservative treatment including anticoagulation, continuous low-flow oxygen inhalation, and antibiotics can be an option.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was treated with anticoagulation therapy and had no further symptoms, including syncope; thus, there was no need for additional interventions. Liang et al 19 suggested that cardiopulmonary embolism should be managed by conservative treatment under close monitoring. In patients who develop mild clinical manifestations with a stable hemodynamic status, conservative treatment including anticoagulation, continuous low-flow oxygen inhalation, and antibiotics can be an option.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic pulmonary embolism due to bone cement utilized to perform transpedicular screw fixation is rare, occurring in 1.4% of isolated cases. [ 6 , 7 , 9 , 11 , 13 , 20 ] Currently, ten publications have reported 13 cases of patients with symptomatic pulmonary embolism due to bone cement. [ 1 , 5 , 9 - 12 , 14 - 16 , 20 ] Most of the patients reported were over 64 years of age and had instrumentation of the lumbar spine [ Table 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 , 7 , 9 , 11 , 13 , 20 ] Currently, ten publications have reported 13 cases of patients with symptomatic pulmonary embolism due to bone cement. [ 1 , 5 , 9 - 12 , 14 - 16 , 20 ] Most of the patients reported were over 64 years of age and had instrumentation of the lumbar spine [ Table 1 ]. Of the 13 cases, one had a fatal outcome, and two required open embolectomy; Where pulmonary cement embolisms involve main arterial trunks or are located in cardiac cavities but the patient is asymptomatic, anticoagulation is recommended for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, while CAPS is being increasingly used, post-CAPS cement leakage is a considerable problem. Cement leakage into the spinal canal can cause spinal cord compression symptoms, including neurologic deficits and pain, while leakage into the epidural vein, vena cava, right atrium, pulmonary artery, or multiple lung arterioles can cause cardiac or pulmonary cement embolism (PCE) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Since both embolisms have the same pathology, this study included cardiopulmonary cement embolisms after CAPS as CPCE.…”
Section: Introductionmentioning
confidence: 99%
“…Heat associated with cement polymerization can also cause neurological damage [ 18 ]. However, only a few publications have reported the incidence of CPCE or CAPS-related complications, most in the form of case reports [ 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. CPCE rates reported in past studies showed a wide prevalence range because it does not have a standard definition, and different studies used different methods to evaluate cement embolism [ 2 ].…”
Section: Introductionmentioning
confidence: 99%